Width effects on downward flame spread over poly(methyl methacrylate) sheets. (January 2015) - Zhao, Kun; Zhou, Xiaodong; Yang, Lizhong; Gong, Junhui; Wu, Zhibo; Huan, Zufei; Liu, Xueqiang
The experiments of downward flame spread over poly(methyl methacrylate) sheets with different dimensions were conducted in this study. In comparison with flame spread over samples under infinite width condition, lateral air entrainment shows significant influence on downward flame spread of finite width. The characteristic angles, defined as those produced on sample residues in a steady-state stage, are constant for different dimensions. Based on the characteristic angles and with reasonable assumptions, a three-dimensional theoretical model is proposed to illustrate the experimental results. Width effects on downward flame spread over thicker samples are more obvious and they fade away with gradual increase in width. Moreover, the heat flux penetrating through the solid surface at the front of the pyrolysis region is higher than that in the two-dimensional case. The flame height correlates well with mass loss rate as an exponential function with a mean power value of 0.79.